Impact of later retirement on mortality: Evidence from France - Antoine Bozio; Clémentine Garrouste; Elsa Perdrix (Health Economics, 2021)
This paper investigates the impact of delaying retirement on mortality among the French population. We take advantage of the 1993 pension reform in the private sector to identify the causal effect of an increase in claiming age on mortality. We use administrative data which provide detailed information on career characteristics, dates of birth and death. Our results, precisely estimated, show that an exogenous increase of one year in the claiming age has no significant impact on the probability to die, measured between age 61 and 79, even when we allow for nonlinear effects of treatment intensity. To test the power of our sample to detect statistically significant effects for rare events like death, we compute minimum detectable effects (MDEs). Our MDE estimates suggest that, if an impact of later retirement on mortality would be detectable, it would remain very small in magnitude.
Keywords: 330; health; mortality; pension reform